2017
DOI: 10.1177/1029864917701536
|View full text |Cite
|
Sign up to set email alerts
|

Trait Empathy associated with Agreeableness and rhythmic entrainment in a spontaneous movement to music task: Preliminary exploratory investigations

Abstract: The simulation theory of empathy suggests that we use motor processing to empathise, through modelling the actions of others. Similarly, research into embodied music cognition posits that music, particularly musical rhythm, is perceived as a motor stimulus. In both cases, the human Mirror Neuron System (MNS) is put forward as a potential underlying mechanism. If this is the case, some overlap may exist between the ability to empathise with others, and the ability to perceive rhythm in music. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 69 publications
(102 reference statements)
3
31
0
2
Order By: Relevance
“…For example, children with higher social capacities were found to synchronize better in a dyadic drumming task than children low on social skills [ 63 ]. Similarly, high empathy has been linked to rhythmic coordination with people high on trait empathy found to entrain movements quicker to a rhythmic stimulus than those low on trait empathy [ 64 ]. Enhanced sensitivity for synchronous aspects of chanting practice is likely to facilitate the experience of altered states by increasing the salience and intensity of repetitive rhythmic stimuli [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, children with higher social capacities were found to synchronize better in a dyadic drumming task than children low on social skills [ 63 ]. Similarly, high empathy has been linked to rhythmic coordination with people high on trait empathy found to entrain movements quicker to a rhythmic stimulus than those low on trait empathy [ 64 ]. Enhanced sensitivity for synchronous aspects of chanting practice is likely to facilitate the experience of altered states by increasing the salience and intensity of repetitive rhythmic stimuli [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible interpretation could be related to rhythmic entrainment. The cerebellum is involved in the neural tracking of rhythm (e.g., Nozaradan et al, 2017 ), and trait empathy is positively associated with (sensorimotor) rhythmic entrainment abilities (e.g., Bamford & Davidson, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that an individual’s tendency to use empathy (i.e. the ability to interpret and understand others’ thoughts and feelings) relates to their ability to adjust to sudden tempo changes 16 , and to their adjustment of body movement in response to different partners in a dyadic dance context 10 . However, these studies did not measure social perception of movement, and moreover relied on fairly limited analysis of full body movement.…”
Section: Introductionmentioning
confidence: 99%